Notch Dosage: Jagged1 Haploinsufficiency Is Associated With Reduced Neuronal Division and Disruption of Periglomerular Interneurons in Mice - Blackwood, Christopher A.; Bailetti, Alessandro; Nandi, Sayan; Gridley, Thomas; Hébert, Jean M. (Frontiers in Cell and Developmental Biology, 2020)
Neural stem cells in the lateral ganglionic eminence (LGE) generate progenitors that migrate through the rostral migratory stream (RMS) to repopulate olfactory bulb interneurons, but the regulation of this process is poorly defined. The evolutionarily conserved Notch pathway is essential for neural development and maintenance of neural stem cells. Jagged1, a Notch ligand, is required for stem cell maintenance. In humans, heterozygous mutations in JAGGED1 cause Alagille syndrome, a genetic disorder characterized by complications such as cognitive impairment and reduced number of bile ducts in the liver, suggesting the presence of a JAGGED1 haploinsufficient phenotype. Here, we examine the role of Jagged1 using a conditional loss-of-function allele in the nervous system. We show that heterozygous Jagged1 mice possess a haploinsufficient phenotype that is associated with a reduction in size of the LGE, a reduced proliferative state, and fewer progenitor cells in the LGE and RMS. Moreover, loss of Jagged1 leads to deficits in periglomerular interneurons in the olfactory bulb. Our results support a dose-dependent role for Jagged1 in maintaining progenitor division within the LGE and RMS.